2015
DOI: 10.1155/2015/521584
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Antibiotics and Antifungal Medicinal Products: Can Complementary and Alternative Medicine Help Solve the Problem in Common Infection Diseases? The Introduction of a Dutch Research Consortium

Abstract: The increase of antibiotic resistance worldwide, rising numbers of deaths and costs associated with this, and the fact that hardly any new antimicrobial drugs have been developed during the last decade have increased the interest in Complementary and Alternative Medicine (CAM) therapeutic interventions, if proven safe and effective. Observational studies on clinical CAM practices demonstrate positive effects of treatment of infections with CAM therapies (clinical effects, patient satisfaction) in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Finally, despite the necessity of more adequately powered clinical studies, the findings of the study have excitingly indicated the clinical benefits of chemo-immunotherapy in the management of vaginal candidiasis. Such an approach has been shown to accelerate the recovery as well as reduce the recurrence of the disease [78].…”
Section: Vaginal Candidiasismentioning
confidence: 99%
“…Finally, despite the necessity of more adequately powered clinical studies, the findings of the study have excitingly indicated the clinical benefits of chemo-immunotherapy in the management of vaginal candidiasis. Such an approach has been shown to accelerate the recovery as well as reduce the recurrence of the disease [78].…”
Section: Vaginal Candidiasismentioning
confidence: 99%
“…The empirical use of plants for treating diseases produced by Candida in different parts of the world possesses a long history (Höfling et al, 2011); at present, the increased use of this type of Medicine could be a consequence of the resistance of pathogen agents to pharmaceutical antibiotics (van Minnebruggen et al, 2010). Different pharmacological in vitro evaluations and clinical trials have confirmed the antifungal properties of extracts obtained from the plant species A. pichinchensis (Castañeda et al, 1996;Romero et al, 2006;Kok et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Together with vaccination and public health measures, antibiotics have played an important role in the drastic reduction of the mortality rate from infectious diseases [1]. However, from the first application of penicillin in practical medicine, humanity was faced with the serious problem of the antimicrobial resistance (AMR) occurrence.…”
Section: Issn 2308-8303mentioning
confidence: 99%